Economic Activities of Rose Sasirangan MSME in Banjarmasin - Putri Imaniyati; Syaharuddin Syaharuddin; Raihanah Sari; Sovia Husni Rahmia; Sigit Triyono (Universitas Lambung Mangkurat, 2026)
Sasirangan cloth is a cultural heritage of South Kalimantan. As time goes by, Sasirangan cloth faces the challenge of competition. Craftsmen need to innovate in producing new, attractive products. The purpose of this study is to analyze the production, distribution, and consumption activities at the Rose Sasirangan MSME. The research method used is a qualitative method with observation techniques on production, distribution, and consumption activities. This research is also supported by interviews with informants consisting of the owner of the Rose Sasirangan MSME, Craftsmen, retailers, and buyers. The results show that the production of Sasirangan cloth at Rose Sasirangan is carried out collaboratively with craftsmen in Sasirangan Village, with production locations spread across the craftsmen's homes due to limited space and the smell of waste. Products sold include metered cloth and processed sasirangan cloth such as bags, wallets, sandals, tissue boxes, caps, and laying through a consignment and barter system with craftsmen in Zafri Zam-Zam and Sungai Andai. Then the distribution activities are carried out directly through stores, WhatsApp where information is shared through business cards, and expeditions (J&T, Tiki, Pos, JNE), and indirectly through intermediaries. And Sasirangan is consumed as a cultural symbol of the Banjarmasin community, used in various forms such as clothing, uniforms, and accessories and is in demand by various groups. The conclusion of this study is that sasirangan cloth is known as South Kalimantan's cultural heritage that continues to be preserved amidst the challenges of modernization. Rose Sasirangan carries out production collaboratively, distributes products through various channels and maintains the culture of sasirangan. They also collaborate with craftsmen around Sasirangan Village to innovate in design and products, in order to expand the market to young people who are declining interest in sasirangan cloth.